Testing of library preparation methods for transcriptome sequencing of real life glioblastoma and brain tissue specimens: A comparative study with special focus on long non-coding RNAs - Vecera, Marek; Sana, Jiri; Oppelt, Jan; Tichy, Boris; Alena, Kopkova; Lipina, Radim; Smrcka, Martin; Jancalek, Radim; Hermanova, Marketa; Kren, Leos; Slaby, Ondrej (PloS one, 2019)
Current progress in the field of next-generation transcriptome sequencing have contributed significantly to the study of various malignancies including glioblastoma multiforme (GBM). Differential sequencing of transcriptomes of patients and non-tumor controls has a potential to reveal novel transcripts with significant role in GBM. One such candidate group of molecules are long non-coding RNAs (lncRNAs) which have been proved to be involved in processes such as carcinogenesis, epigenetic modifications and resistance to various therapeutic approaches. To maximize the value of transcriptome sequencing, a proper protocol for library preparation from tissue-derived RNA needs to be found which would produce high quality transcriptome sequencing data and increase the number of detected lncRNAs. It is important to mention that success of library preparation is determined by the quality of input RNA, which is in case of real-life tissue specimens very often altered in comparison to high quality RNA commonly used by manufacturers for development of library preparation chemistry. In the present study, we used GBM and non-tumor brain tissue specimens and compared three different commercial library preparation kits, namely NEXTflex Rapid Directional qRNA-Seq Kit (Bioo Scientific), SENSE Total RNA-Seq Library Prep Kit (Lexogen) and NEBNext Ultra II Directional RNA Library Prep Kit for Illumina (NEB). Libraries generated using SENSE kit were characterized by the most normal distribution of normalized average GC content, the least amount of over-represented sequences and the percentage of ribosomal RNA reads (0.3-1.5%) and highest numbers of uniquely mapped reads and reads aligning to coding regions. However, NEBNext kit performed better having relatively low duplication rates, even transcript coverage and the highest number of hits in Ensembl database for every biotype of our interest including lncRNAs. Our results indicate that out of three approaches the NEBNext library preparation kit was most suitable for the study of lncRNAs via transcriptome sequencing. This was further confirmed by highly consistent data reached in an independent validation on an expanded cohort.
Keywords: regulace genové exprese u nádorů; sekvenční analýza RNA; reagenční diagnostické soupravy; High-Throughput Nucleotide Sequencing; Gene Expression Regulation, Neoplastic; nádory mozku; lidé; stanovení celkové genové exprese; glioblastom; Glioblastoma; RNA, Long Noncoding; genová knihovna; vysoce účinné nukleotidové sekvenování; Gene Library; Brain Neoplasms; RNA dlouhá nekódující; Sequence Analysis, RNA; Gene Expression Profiling; Reagent Kits, Diagnostic; Humans